THE DEVELOPMENT OF SOCIO-ECONOMIC GEOGRAPHY IN THE RA. KEY DIRECTIONS AND OUTCOMES - Potosyan, Aksel H. (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Geographical research plays a crucial role in the economic development of countries and serves as an essential tool for territorial planning and organization. Over the past decades, comprehensive socio-economic and geographical studies have been conducted in Armenia to align with the country's economic development needs. These studies have identified the geographical characteristics of Armenia's natural environment and resources, population and settlements, settlement patterns, economic distribution, and territorial organization. They have played a direct role in shaping various economic programs, resource management, production distribution, and territorial development processes in the Republic of Armenia. This article aims to summarize the key directions of socio-economic and geographical research conducted in Armenia over recent decades and to highlight their main findings. Географические исследования играют ключевую роль в экономическом развитии стран, выступая важным инструментом территориального планирования и общественного прогресса. В последние десятилетия в Республике Армения, в соответствии с потребностями экономического роста, проводились комплексные социально-экономико-географические исследования. Они позволили выявить особенности природного комплекса и ресурсов страны, характеристики населения и населенных пунктов, систему расселения, структуру хозяйства и территориальную организацию. Полученные данные внесли значительный вклад в разработку программ экономического развития, рациональное использование ресурсов, размещение производств и совершенствование территориального планирования. В статье ставится задача обобщить основные направления социально-экономико-географических исследований, проведенных в РА за последние десятилетия, и представить их основные результаты. Աշխարհագրական հետազոտություններն իրենց անմիջական դերն ունեն երկրների տնտեսական զարգացման գործում և համարվում են կարևորագույն գործիք հասարակության տարածքային կազմակերպման ու զարգացման գործընթացներում: Անցած տասնամյակների ընթացքում ՀՀ-ում՝ տնտեսության զարգացման պահանջներին համապատասխան իրականացվել են նաև սոցիալ-տնտեսաաշխարհագրական համալիր հետազոտություններ: Վեր են հանվել ՀՀ բնական համալիրի տարրերի ու ռեսուրսների,  բնակչության ու բնակավայրերի, տարաբնակեցման, տնտեսության տեղաբաշխման ու տարածքային կազմակերպման աշխարհագրական առանձնահատկությունները: Դրանք իրենց անմիջական դերն են ունեցել ՀՀ-ում տնտեսական զարգացման տարբեր ծրագրերի մշակման, ռեսուրսների շահագործման, արտադրության տեղաբաշխման և զարգացման գործընթացներում: Հոդվածում խնդիր է տրվել ընդհանրացնել անցած տասնամյակների ընթացքում ՀՀ-ում կատարված սոցիալ-տնտեսաաշխարհագրական հետազոտությունների հիմնական ուղղությունները և մատնանշել արդյունքները: